An empirical analysis of producer prices in the dairy sector in Argentina: what can we expect from milk processing cooperatives? = Un análisis empírico de los precios de producción en el sector lácteo en Argentina - Puechagut, Maria Soledad; Malvido Perez Carlet, Agustina; Gastaldi, Laura Beatriz (2017)
Este trabajo fue presentado en el International Research Conference "New Strategies for Co-operatives: Understanding and Managing Co-operative Creation, Transition and Transformation" 2016. Almeria, 24th to 27th May, 2016